EVALUATION OF PHYSICO CHEMICAL CHARATERISTICS OF SILK FIBRES OF Litsea cubeba Pers., REARED ON DIFFERENT HOST PLANTS - Hamzah, Faizah (Universitas Andalas, 2008)
ABSTRACT The golden-yellow silk fibres obtained from Litsea cubeba Pers., westwood reared on leaves of three different host plants belonging to the family Lauraceous, were studied to evaluate their characteristic physico – chemical properties. The host plants M. bombycina King, L. cubeba Pers., Juss and L. citrate Roxby, significantly influenced silk length, width, sericin and amino acid contents of the fibres. The contents of the predominant amino acid; glycine (10.55 μg), aspartic (5.43 μg) and (7.15 μg), were higher in fibres obtained from cocoons of L. cubeba Pers., fed on M. bombycina, while alanine (9.46 μg) was higher in the fibres of cocoons obtained from the two host plant. The breaking load (17.191 g) and tenacity (3.562 g) were higher in cocoons from the host plant L. cubeba Pers. The X-ray diffraction patterns showed the amorphous nature of the fibres obtained from the cocoons of L. cubeba Pers., fed on L. polyantha and L. citrate while fibres obtained from cocoons from M.bombycina showed amorphous bands with little tendency to two dimensional order. Above all, the natural golden yellow hue of the fibre, which is one of the most important and commercially valuable added properties of this particular silk variety, was better retained in the fibres extracted from cocoons of L. cubeba Pers., larvae reared on M. bombycine. Keywords : amino acids, breaking load, L. cubeba Pers., tenacity, x-ray diffraction